KETERLIBATAN GURU DALAM PENGUATAN LITERASI MEMBACA INDIVIDU DAN KELOMPOK SISWA SEKOLAH DASAR KELAS AWAL - Santika Buwana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading ability in the early grades of elementary school is a crucial foundation for student learning success. However, the heterogeneity of reading abilities within a single classroom presents a real challenge for teachers, particularly in designing responsive and differentiated instruction. This study aims to deeply examine teacher involvement in strengthening individual and group reading literacy in early-grade elementary school classrooms. The research employed a qualitative approach with a case study design. Participants consisted of two early-grade teachers purposively selected from SD Inpres 48 Sorong Regency, referred to by the initials GS1 and GS2. Data were collected through in-depth semi-structured interviews. The findings indicate that both teachers demonstrated a good awareness of the diversity in students' reading abilities and implemented continuous informal assessments using learning books and reading cards. Both teachers applied clear differentiation strategies: students who were already fluent readers were given independent tasks, while those not yet fluent received intensive support through reading conferences held 1–3 times per week. GS2 also implemented a peer tutoring approach and used picture story media for students experiencing difficulties. Feedback was provided in a differentiated manner according to students' ability levels. In group learning, groups were formed based on initial assessment results, with productive classroom management. The main challenges included limited textbooks, gaps in student abilities, lack of learning media, and insufficient family support. It is concluded that strengthening early-grade reading literacy requires a comprehensive approach that encompasses ongoing formative assessment, differentiated instruction, and active collaboration among teachers, schools, and families.